Stratigraphic correlation of Holocene phonolitic explosive episodes of the Teide-Pico Viejo Complex, Tenerife - Garcia, Olaya (2014)
Teide and Pico Viejo (TPV) are twin stratovolcanoes that form one of the largest alkaline volcanic complexes in the world. They began forming inside the caldera of Las Cañadas about 200 ka ago and are largely made up of an accumulation of mafic, intermediate and more recent felsic products that form lava flows. However, a significant number of Holocene pyroclastic deposits are also present. To quantify the explosive contribution to the construction of TPV, we re-examined its stratigraphy and identified several Holocene phonolitic explosive episodes ranging from Strombolian to sub-Plinian styles that are represented by fallout and pyroclastic density current deposits. Although some of the pumice deposits have been related to known sources, a few have not been linked to a specific vent. The use of field data as well as geochemical and mineralogical analysis helped to provide reliable criteria for robust correlations and to establish the relative stratigraphy of the deposits. The presence of these pyroclastic deposits in the recent history of the TPV complex suggests that these stratovolcanoes are entering a more explosive stage that represents a nonavoidable hazard for the island of Tenerife.